1997
DOI: 10.1007/s002570050520
|View full text |Cite
|
Sign up to set email alerts
|

Heat transport in the insulating phases of Sm1+x Ba2-x Cu3Oy high temperature superconductors

Abstract: Thermal conductivity (κ) of two series of hightemperature superconductors with general formula Sm 1+x Ba 2−x Cu 3 O y have been measured. Both series begin with the same sample of T c = 90.4 K and extend to nonsuperconducting phases. The first series is of 123 cation stoichiometry and variable oxygen content y, the second is a series of solid solutions with variable x. The temperature dependences of κ are very similar for superconducting partner samples from both series (i.e. with the same T c ), whereas the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…It can be either an electronic contribution or phononic contribution due to the decrease in phonon-carrier scattering and an increase in the phonon free path or both of them could be effective. Although, resent works on the similar HT c materials showed that the sharp increase of κ gives an evidence of the quasi-particle effect to the heat conductivity and also an increase of the quasi-particle mean free path [37,39,42,46,[75][76][77][78][79].…”
Section: Xin's Two Band Modelmentioning
confidence: 95%
“…It can be either an electronic contribution or phononic contribution due to the decrease in phonon-carrier scattering and an increase in the phonon free path or both of them could be effective. Although, resent works on the similar HT c materials showed that the sharp increase of κ gives an evidence of the quasi-particle effect to the heat conductivity and also an increase of the quasi-particle mean free path [37,39,42,46,[75][76][77][78][79].…”
Section: Xin's Two Band Modelmentioning
confidence: 95%
“…As mentioned in the first section, it can be either an electronic contribution or caused by the reduction of the phonon scattering mechanism or both. However, in the recent studies, both on theoretical and experimental on the high-T c materials, showed that the increase of κ just below T c gives an evidence for enhancement of the quasiparticle contribution to the heat conductivity and so an increase of the quasi-particle mean free path [32,34,37,41,[72][73][74][75][76][77][78], where the main source of the quasi-particle scattering in the high-T c materials is electronic in origin.…”
Section: Thermal Conductivity κ(T)mentioning
confidence: 96%
“…It is found in the recent theoretical and experimental studies that the sharp rise in j(T) just below T c shows the enhancement of the quasiparticle contribution to the heat conductivity: Quasiparticle life-time and quasiparticle mean free path abruptly increase in the superconducting state. This causes increase in the electronic heat transport [39][40][41].…”
Section: Heat Treatment Temperature (°C)mentioning
confidence: 98%